The scope of upper limb surgery for tetraplegics: Role of tendon transfers and Universal Cuff - Mukul Mohindra; Paritosh Gogna; Sukhbir Singh Sangwan; Sahil Gaba; Zile Singh Kundu (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to evaluate the role of tendon transfers and universal cuff in restoring hand function in tetraplegic patients. Methods: Twenty-one upper limbs on 12 tetraplegic patients (9 males and 3 females); mean age: 42.2 years (range 22–58 years) with a spinal cord injury at or distal to C6, were included in this study. Key pinch was restored using Brachioradialis to Flexor Pollicis Longus transfer and hook using Pronator Teres to Flexor Digitorum Profundus transfer. The gains achieved were measured objectively at six months and at final follow up, the average follow up being 26 months. The functional outcome was assessed using the Modified Lamb and Chan score. Results: Average value was 1.67 kg for key pinch and 2.58 kg for hook grip at final follow up. The Modified Lamb and Chan score revealed good to fair outcome in 75% of patients. Complications resulted from stretching of transfer and mal-tensioning and were salvaged by the use of a ‘Universal Cuff’. Conclusion: Surgery should be routinely offered to tetraplegic patients with deficient hand function in whom no recovery is expected after six months following spinal cord injury. Universal Cuff is a good salvage method for patients who refuse re-surgery. Level of evidence: Level IV, Therapeutic study. Keywords: Tendon transfers in tetraplegia, Spinal cord injury, Universal Cuff, Lamb and Chan score